Bridging Biological Multiscale Structure and Biomimetic Ceramic Construction - Jingjiang Wei; Tianyu Yuan; Hang Ping; Fei Pan; Zhengyi Fu (Research)
The brittleness of traditional ceramics severely limits their application progress in engineering. The multiscale structural design of organisms can solve this problem, but it still lacks sufficient research and attention. The underlined main feature is the multiscale hierarchical structures composed of basic nano–microstructure units arranged in order, which is currently impossible to achieve through artificial synthesis driven by high temperatures. This perspective aims to bridge the gap between biostructural materials and biomimetic ceramics, highlighting the relationship between bioinspired structures and interfacial interaction of structure densification in biomimetic ceramics. Therefore, we could accomplish densification and ceramic development at room temperature, consequently correlating the structure, properties, and functions of materials and accelerating the development of the next generation of advanced functional ceramics.